2019
DOI: 10.1093/mnras/stz3357
|View full text |Cite
|
Sign up to set email alerts
|

CHILES VI: H i and H α observations for z < 0.1 galaxies; probing H i spin alignment with filaments in the cosmic web

Abstract: We present neutral hydrogen (H i) and ionized hydrogen (H α) observations of 10 galaxies out to a redshift of 0.1. The H i observations are from the first epoch (178 h) of the COSMOS H i Large Extragalactic Survey (CHILES). Our sample is H i biased and consists of 10 late-type galaxies with H i masses that range from 1.8 × 107 M⊙ to 1.1 × 1010 M⊙. We find that although the majority of galaxies show irregularities in the morphology and kinematics, they generally follow the scaling relations found in larger samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 80 publications
4
16
0
Order By: Relevance
“…Only a handful of studies have investigated the correlation between HI mass and distance from the spine of large-scale structure filaments, and samples are still relatively small and generally biased towards gas-rich systems. While there seems to be common agreement that gas richness may vary with distance from the filaments (Kleiner et al 2017;Crone Odekon et al 2018;Blue Bird et al 2020), additional work is needed to properly quantify these differences and their dependence on galaxy properties. For example, while Crone Odekon et al (2018) find an increase of HI content with increasing distance from the spine of the large-scale structure, Kleiner et al (2017) report the opposite trend for galaxies with stellar masses greater than 10 11 M .…”
Section: Large-scale Structure Filamentsmentioning
confidence: 99%
“…Only a handful of studies have investigated the correlation between HI mass and distance from the spine of large-scale structure filaments, and samples are still relatively small and generally biased towards gas-rich systems. While there seems to be common agreement that gas richness may vary with distance from the filaments (Kleiner et al 2017;Crone Odekon et al 2018;Blue Bird et al 2020), additional work is needed to properly quantify these differences and their dependence on galaxy properties. For example, while Crone Odekon et al (2018) find an increase of HI content with increasing distance from the spine of the large-scale structure, Kleiner et al (2017) report the opposite trend for galaxies with stellar masses greater than 10 11 M .…”
Section: Large-scale Structure Filamentsmentioning
confidence: 99%
“…There have also been extensions of such studies beyond the local universe (e.g. Catinella et al 2008;Catinella & Cortese 2015;Verheijen et al 2007;Hess et al 2019;Bera et al 2019;Blue Bird et al 2020;Gogate et al 2020). How-ever, even with very deep integrations, direct detections of H i in emission have so far been from gas-rich, star-forming galaxies (≥2 × 10 9 M ; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The first robust observational evidence was provided by the Tempel, Stoica & Saar (2013) and Tempel & Libeskind (2013), who have shown that the spins of spiral galaxies are preferentially aligned with the filament axis while the minor axis of elliptical galaxies, which are typically of higher mass, is preferentially perpendicular to the filaments axis (see also Hirv et al 2017). The same trend, although at a lower statistical significance due to the smaller sample, is seen when inferring the spin from the stellar or gaseous velocity maps, such as those obtained using SAMI or MaNGA (Krolewski et al 2019;Blue Bird et al 2020;Welker et al 2020).…”
mentioning
confidence: 80%